Balancing cultural plurality and national unity through education : the case of Malaysia - Hashim, Rosnani (IIUM Press, International Islamic University Malaysia, 2005)
This paper analyzes the attempt made by the Malaysian educational authority to maintain a balance between the need for national unity and the need to preserve cultural diversity among its multi-cultural population. Striking the right balance in a civic society is a virtue and this problem is not only true for Malaysia but for any multi-cultural society as the world gets more globalized. Primary education in Malaysia is conducted in three types of national schools, each using the pupils' mother tongue- Malay, Mandarin and Tamil- as the medium of instruction. This is to accommodate and preserve the diverse cultures. However, in view of the nation's aspiration toward national unity, secondary and tertiary education are conducted using Malay as the medium of instruction. The paper analyzes how basic issues of a common language, affirmative action for the under privileged race, a common school have united or divided the nation. it also examines the extent to which these educational efforts have met the goal of balancing national unity and cultural diversity. Finally, the paper looks at the problems and challenges faced by the Malaysian educational authority and suggests ways to improve the situation.